The Inflammasome Adaptor ASC Intrinsically Limits CD4+ T-Cell Proliferation to Help Maintain Intestinal Homeostasis - Javanmard Khameneh, Hanif; Leong, Keith Weng Kit; Mencarelli, Andrea; Vacca, Maurizio; Mambwe, Bezaleel; Neo, Kurt; Tay, Alice; Zolezzi, Francesca; Lee, Bernett; Mortellaro, Alessandra (Frontiers in Immunology, 2019)
The inflammasome is a multi-protein complex that mediates proteolytic cleavage and release of the pro-inflammatory cytokines IL-1b and IL-18, and pyroptosis — a form of cell death induced by various pathogenic bacteria. Apoptosis-associated speck-like protein containing a CARD (ASC) has a pivotal role in inflammasome assembly and activation. While ASC function has been primarily implicated in innate immune cells, its contribution to lymphocyte biology is unclear. Here we report that ASC is constitutively expressed in naïve CD4+ T cells together with the inflammasome sensor NLRP3 and caspase-1. When adoptively transferred in immunocompromised Rag1-/- mice, Asc-/- CD4+ T cells exacerbate T-cell-mediated autoimmune colitis. Asc-/- CD4+ T cells exhibit a higher proliferative capacity in vitro than wild-type CD4+ T cells. The increased expansion of Asc-/- CD4+ T cells in vivo correlated with robust TCR-mediated activation, inflammatory activity, and higher metabolic profile towards a highly glycolytic phenotype. These findings identify ASC as a crucial intrinsic regulator of CD4+ T-cell expansion that serves to maintain intestinal homeostasis.